"No matter if you're a Democrat or a Republican or neither": Pragmatic politics in opposition to industrial animal production. (February 2021) - Ashwood, Loka
Abstract: Scholars call for unusual, visionary pathways forward to counter authoritarian control in situations of helplessness and inequality. Popular strategies for change in such contexts often call for large-scale state interventions achieved through party-line politics. This paper examines two groups that stopped the construction of industrial hog facilities in the United States and finds that rural emancipation comes through direct action, with the state as a secondary, rather than primary, vehicle for change. Pragmatic rural politics predicated on immediate concerns and pathways for action underscore effective protest against corporate agribusinesses. Those involved pursue ends rooted in their shared commitment to a livable and prosperous rural future. Highlights: Electoralism poses distinct barriers to rural emancipation. Pragmatic rural politics work across party lines. Mutual aid enables direct action in conditions of extraction and exploitation. Non-regulatory institutions can help those with anti-state, stateless, and pro-state positions work together.